EFFECTS OF SUPERCRITICAL CO2 ON COMPRESSIVE STRENGTH AND POROSITY OF GEOPOLYMER CEMENT UNDER ELEVATED TEMPERATURE AND PRESSURE - SETIAWAN, RIAU ANDRIANA (2019)
Several studies have been conducted to find an alternative cement system for wellbore. Geopolymer cement has been showed potential utilization because it possess many advanced cement properties such as high compressive strength, low shrinkage and an excellent resistance to sulphate attack, good acid resistance and low creep.